Autoethnography and artistic creation: an introspective look at the creative process in musical ensembles - Correa Fuentes, Baronio J.; Parga Herrera, Manuel H. (Frontiers in Education, 2025)
In contemporary music studies, urban musical ensembles have shifted from being associated solely with artistic practice to becoming a fertile setting for cultural and pedagogical inquiry. This article examines the collective creative processes within such ensembles through the lenses of autoethnography and research-creation, particularly in contexts characterized by cultural diversity. The study aims to explore how music, beyond its aesthetic dimensions, functions as a site of cultural negotiation and a means of generating knowledge. Drawing on theoretical reflection and critical analysis of documented experiences, the article investigates how musical interaction intertwines group dynamics and individual subjectivities to produce a collective artistic outcome. The findings suggest that urban ensembles operate not merely as performance collectives but as arenas of cultural exchange where communicative tensions act as catalysts for meaningful learning. These tensions, arising from diverse perspectives and experiences, enrich collaboration and foster inclusive environments where creativity thrives on difference. Consequently, the creative process is reinterpreted not only as musical production but also as a pedagogical act, an experience that integrates creation, collaboration, and mutual understanding.